Benefit Sharing in the Arctic Extractive Industries and Arctic People - Tysiachniouk, Maria; Petrov, Andrey N; Gassiy, Violetta (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book provides a first-of-its-kind review and analysis of benefit sharing frameworks between extractive industries and Indigenous and local communities in different parts of the Arctic. The authors describe a wealth of case studies in order to examine predominant practices, policies, arrangements, mechanisms and impact assessment methodologies. They also discuss possible ways to improve and advance existing benefit sharing regimes, in order to attain fair and equitable benefit sharing and support sustainable development. Among the topics covered in the book are corporate social responsibility and social license to operate, principles and methodologies of determining compensation, legal and informal frameworks of benefit sharing, community response to extractive activities, and global-to-local linkages that shape benefit sharing processes. The book will be of interest to academics, industry experts, legal specialists, policymakers, community members concerned with industrial activities, and anyone interested in sustainable development in the Arctic.